Excreta quality and digestive function of singly versus couple caged Sardinian partridges (Alectoris barbara barbara Bonnaterre, 1790) as non‐invasive indicators of birds' coping ability to forced pairing. Issue 4 (20th June 2021) - Ahmed, Fahad; Pudda, Flavia; Muzzeddu, Marco; Schiavone, Achille; Varcasia, Antonio; Nery, Joana; Serra, Giuseppe; Seidavi, Alireza; Cappai, Maria Grazia
Abstract: The Sardinian partridge is a monogamous wild bird species of least concern according to IUCN list at present, though formerly accounted among threatened species for decades. The creation of couples is crucial in captivity, because forced pairing in cages can lead to poor welfare of birds, specially of females. This study investigated the impact of single versus couple caging of Sardinian partridges during non‐laying period based on the collection and interpretation of indirect and non‐invasive parameters (feed intake; space availability; excreta quality; and nutrient utilization). A total of 24 couples of breeding partridges were enrolled for two consequent phases of a same investigation (lasting 15 days each). During phase 1, all couples were fed ad libitum with a pelleted complete diet (DM, 905 g kg −1 of diet; CP, 160 g kg −1 ; and EE, 25 g kg −1 ). In phase 2, each male from 12 out of 24 couples was moved to an identical cage close to that where the female remained alone, to keep visual contact. The rest of couples continued to be kept like in phase 1. During phases 1 and 2, feed intake and excreta outputs were recorded daily. Pooled excreta of the last 3 days from couples and single birds were assessed for pH and DM, CP and ash content. Nutrient digestibility was calculated. No significant differences were noted between single versus couple caging regarding body weight (438 vs. 422 g respectively) or nutrient digestibility. However, singly housed males reduced daily feed intakes and females increased daily feed intake per g −1 BW (0.041 vs. 0.052 g, respectively, p  < 0.001). Our results suggest that singly caged partridges from permanent couples can improve the access to feed and reduce competition during the non‐mating season.